2002
DOI: 10.1149/1.1462037
|View full text |Cite
|
Sign up to set email alerts
|

A Century of Organic Electrochemistry

Abstract: © 2002 The Electrochemical Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
82
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(85 citation statements)
references
References 282 publications
(221 reference statements)
2
82
0
1
Order By: Relevance
“…All results agree with the number of electrons obtained by different authors in the literature [30]: bielectronic (aldehydes and amines) and tetraelectronic (oximes and acids)…”
Section: General Behavioursupporting
confidence: 92%
“…All results agree with the number of electrons obtained by different authors in the literature [30]: bielectronic (aldehydes and amines) and tetraelectronic (oximes and acids)…”
Section: General Behavioursupporting
confidence: 92%
“…The study on verapamil, tamsulosin, and other synthesized indole compounds was realized by CV at GC electrode as a function of pH in order to identify the responsible atom for the second oxidation process of 1u. Our results revealed a good agreement with the redox mechanism postulated for similar compounds such as 4-methoxyphenol, tamsulosin and verapamil suggested that tamsulosin can be determined electrochemically by oxidation of methoxybenzene groups 40,41,45,46 .…”
Section: Electrochemical Measurementssupporting
confidence: 86%
“…The characteristics of the calibration plots are summarized in Table 2. The detection limit and quantification limit of the procedures (Table 2) were calculated according to the 3 s/m and 10 s/m criterions, respectively, where s is the standard deviation of the peak currents (five runs) and m is the slope of related calibration graph [45][46][47] .…”
Section: Analytical Applications and Methods Validationmentioning
confidence: 99%
“…The slope of 63.54 mV per pH was close to the theoretic value 59 mV per pH, suggesting one electron and one proton transferred in the oxidation of diclofenac sodium. The oxidative reaction of diclofenac sodium is a one electron, one-proton transfer process resulting in the radical species [37,38].…”
Section: Effect Of Ph On the Peak Potentials And Peak Currentsmentioning
confidence: 99%